Theoretical Implications for the Analysis of Social Health Inequalities: A Discussion - Barboza-Solís DDS, MSc, PhD, Cristina (2019)
Social health inequalities (or inequities) continue to represent a great challenge for public health research worldwide. Since 1991, the World Health Organization established that the study and analysis of health inequalities represented a priority for all countries. To better guide methodological and practical implications of health inequalities, research on this topic should present a solid theoretical model, able to impact future public health policies.  Previous studies of health inequalities in Latin America are often inspired from abroad experiences, encouraging the reproduction of mainly European theoretical positions and methodologies. However, especially when it comes to  this topic, it is known the important role of the social context and culture, playing an important role in promoting differences in health outcomes. From this perspective, to operationalize the different social determinants in health, a critical perspective and thoughtful analysis of the context is mandatory.  In order to provide a critical analysis and useful tools for both research and health decision making, we recommend that the theoretical and methodological approaches used in social health inequalities research must be well adapted to the specific contexts; that health social stratification must be assessed as a priority; that individual and the wider health determinants must be well characterized; and that the theoretical justification of the methodological decisions made in the studies and the selected measures must be explicit and should answer specific hypotheses.  This research provides a brief historical background, to share the basis for the conceptual evolution of social health inequalities; the main underlying concepts related to the definition of health inequalities (social determinants, equity, justice, stratification and social gradient in health); and some recommendations for the future perspectives of health inequalities research in Latin America.